MITIGATING THE IMPACT OF COVID-19 ON THE FOOD INDUSTRY: LESSONS LEARNED AND FUTURE DIRECTIONS - Norrina Din; Noorliza Zainol; Noorsa Riza Johari; Mohamad Azli Razali (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2023)
The COVID-19 pandemic has affected the global economy and daily life, with the food industry being particularly impacted. The potential transmission of the virus through the food supply chain, including production, processing, distribution, retail, and delivery personnel, raises concerns. Thus, there is an urgent need for a Food Safety Management System that incorporates good hygiene, sanitation, and worker fitness. This proposed conceptual paper aims to scrutinise the knowledge, risk perception and preventive actions among food workers, including food riders, during the COVID-19 pandemic. This study also aims to support the development of a more comprehensive approach to food safety management systems to mitigate the impact of COVID-19 on the food industry. Policymakers could use this data to develop policies to improve preventive measures and guidelines for food service operators, both now and in the future